2008
DOI: 10.1038/cr.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency of generating induced pluripotent stem (iPS) cells from human somatic cells by a combination of six transcription factors

Abstract: Human embryonic stem (ES) cells possess the potential to differentiate into all the cell types of the human body and provide potential applications in regenerative medicine [1]. However, the concerns of immune rejection hamper transplantation therapies using human ES cells. To avoid the complications of immune rejection, diverse methods, such as somatic nuclear transfer (also called therapeutic cloning) and fusion of somatic cells with human ES cells [2], have been attempted to produce patient-specific pluripo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 11 publications
3
101
0
2
Order By: Relevance
“…Simultaneous transduction of c-myc, Oct4, Sox, Klf4, with Nanog and Lin28 increases efficiency dramatically (Liao et al, 2008). Other studies have shown that expression of p53 siRNA and UTF1 dramatically increases iPS colonies .…”
Section: Enhancement Of Ips Productionmentioning
confidence: 94%
“…Simultaneous transduction of c-myc, Oct4, Sox, Klf4, with Nanog and Lin28 increases efficiency dramatically (Liao et al, 2008). Other studies have shown that expression of p53 siRNA and UTF1 dramatically increases iPS colonies .…”
Section: Enhancement Of Ips Productionmentioning
confidence: 94%
“…Although all three are required for pluripotency, Nanog overexpression is not required for induced pluripotency. Adding Nanog to the mix, however, increases reprogramming, as does combining the Yamanaka and Thomson reprogramming repertoires (Liao et al, 2008). Fig.…”
Section: Molecular Mechanisms Of Induced Pluripotencymentioning
confidence: 99%
“…Partially different set of factors (OCT4, SOX2, NANOG and LIN28) has been reported to be sufficient to reprogram human fibroblasts [18]. For human foreskin fibroblasts, a combination of six transcription factors (OCT4, NANOG, SOX2, LIN28, C-MYC and KLF4) has been shown to significantly increase the reprogramming efficiency [46]. Interestingly, Scholer and his colleagues [22] have demonstrated that OCT4 alone was able to convert human neural stem cells into iPS cells, termed as "one factor (1F) iPS".…”
Section: Reprogramming Genesmentioning
confidence: 99%